Implementasi Program Penguatan Psikologis melalui Kombinasi Safety Box Art Therapy dan Hypnosis Lima Jari dalam Mengatasi Kecemasan Remaja menjelang Ujian Akhir Nasional - Ike Mardiati Agustin; Siti Nur Qomariyah; Sri Sutriani; Tiara Shinta Dewi; Zahrotul Asfia; Mamik Alfiani; Wahyu Dwi P N (Yayasan Inspirasi El Burhani, 2023)
Introduction: The age phase in life has special characteristics that distinguish one age phase from another, including in the adolescent phase, usually this phase will experience changes in the form of increased adolescent emotions, feeling depressed, feeling lonely easily, excessive anxiety caused by stressors, wrong the only final exam during their study period, so a program is needed that can reduce the anxiety experienced by adolescents through the implementation of a psychological strengthening program with a combination of safety box art therapy and 5 finger hypnosis. Objective: the aim of this service was the success and effectiveness of a youth psychological strengthening program in overcoming anxiety before final exams through a combination of Safety box art therapy and 5 finger hypnosis. Method: This public service was conducted to 66 students of SMP Muhammadiyah Gombong, conducted for 1 month, duration of activities 3 times in 1 week providing a combination of safety box art therapy and 5 finger hypnosis with 45 minutes of therapy time, measuring pre and post anxiety using instruments DASS (Depression Anxiety Stress Scale). Results: The results of the activity showed that there was a decrease in the level of anxiety of students before being given therapy, the average experienced moderate anxiety after being given it decreased to an average of mild anxiety. Conclusion: This program is recommended as an effort to overcome anxiety in adolescents before exams